KAJIAN ALIH FUNGSI RUANG TERBUKA HIJAU DI KOTA DENPASAR - Riana, I Nengah; Widiastuti, Widiastuti; Primayatna, Ida Bagus Gde (RUANG: Jurnal Lingkungan Binaan (SPACE: Journal of the Built Environment); Vol 1 No 1 (2014): April 2014, 2014)
Abstract Denpasar city is both the capital as well as the major growth center in Bali. This growth however has caused problems for open space provision. Green open space in urban areas is a necessary part of spatial planning in order to maintain water catchment areas to improve urban environmental compatibility, creation of an urban environment that is safe, comfortable, fresh, beautiful and healthy, and to provide a balance between the natural environment, the built environment and the public realm. The transformation of open space to urban uses in cities is ubiquitous and impacts on spatial planning. This study aims to determine the extent of land conversion in Denpasar and the reasons for such change. Quantitative analysis is used to focus on the form of land use change and the logic behind it. The study concentrates on open space conversion. Data was collected by observation, questionnaires and interview. The final results of this research will hopefully enrich the field of regional development and urban spatial planning, and provide a useful stimulus in the forward planning of Denpasar. Preliminary results suggest that land conversion predominantly serves residential land use (94.12%). Dominant factors that affect its transfer are due to its strategic location (69.50%) and blocked irrigation channels (30.1%). The analysis demonstrates that many open green spaces are located in strategic areas with a complete infrastructure that supports land conversion but are located beside irrigation channels than cannot function optimally. Keywords: land conversion, green open space, urban open space Abstrak Denpasar merupakan ibu kota Provinsi dan pusat pertumbuhan di Bali. Pesatnya pertumbuhan kota memunculkan permasalahan terkait pengadaan ruang terbuka hijau. Ruang terbuka hijau pada kawasan perkotaan merupakan bagian dari penataan ruang kota dengan tujuan menjaga ketersediaan lahan, sebagai kawasan resapan air, menjaga keseimbangan antara lingkungan alam dan lingkungan binaan, meningkatkan keserasian lingkungan perkotaan, menciptakan lingkungan perkotaan yang aman, nyaman, segar, indah dan bersih. Fenomena alih fungsi banyak terjadi di kota-kota besar dan berdampak pada tata ruang kota secara menyeluruh. Penelitian ini bertujuan untuk mengetahui fenomena alih fungsi lahan yang terjadi di kota Denpasar dan alasan akan terjadinya perubahan ini. Denga menerapkan pendekatan kuantitatif, penelitian ini memfokus kajiannya pada: jenis alih fungsi, faktor mempengaruhi alih fungsi, dan faktor dominan yang mempengaruhi alih fungsi ruang terbuka hujau di Kota Denpasar. Data diperoleh dengan melakukan observasi, penyebaran kuesioner dan wawancara. Hasil analisis menunjukan bahwa mayoritas alih fungsi dilakukan untuk pemenuhan kebutuhan tempat tinggal (94,12%). Sedangkan faktor yang mempengaruhi alih fungsi adalah lokasi yang strategis (69,50%) dan saluran irigasi tidak berfungsi dengan maksimal (30,1%). Alih fungsi ini juga didorong karena ruang terbuka hijau banyak berlokasi di kawasan strategis dengan infrastruktur yang lengkap sehingga menarik masyarakat untuk melakukan alih fungsi, khususnya jika saluran irigasi yang ada tidak bisa difungsikan secara optimal. Kata kunci: alih fungsi, ruang terbuka hijau, ruang terbuka perkotaan
Keywords: alih fungsi; ruang terbuka hijau; ruang terbuka perkotaan